Bits and q-bits as versatility measures - Piqueira,José R.C. (2004)
Using Shannon information theory is a common strategy to measure any kind of variability in a signal or phenomenon. Some methods were developed to adapt information entropy measures to bird song data trying to emphasize its versatility aspect. This classical approach, using the concept of bit, produces interesting results. Now, the original idea developed in this paper is to use the quantum information theory and the quantum bit (q-bit) concept in order to provide a more complete vision of the experimental results.